Pengaruh Perception of Organizational Politics, Emotional Intelligence, dan Transformational Leadership Terhadap Job Performance Melalui Job Satisfaction - Novita, Indah; Edastama, Primasatria (MES Bogor, 2025)
This research aims to analyze the influence of perception of organizational politics, emotional intelligence, and transformational leadership on job performance through the mediating role of job satisfaction. The approach in this research uses quantitative research. Sample collection in this study used a purposive sampling method so that there were 270 respondents in this study. The population of this sample is employees at staff level who work in manufacturing companies, who have become permanent employees, have worked for at least 2 years, and are located in the Tangerang, Jakarta, Bekasi areas. The data analysis technique in this research is using the Structural Equation Model (SEM) with SmartPLS 4.0. The findings in this study show that emotional intelligence, transformational leadership and perception of organizational politics are positively related to job performance. emotional intelligence, transformational leadership, and perception of organizational politics are positively related to job satisfaction. Meanwhile, job satisfaction mediates the relationship between transformational leadership and job performance. And finally, job satisfaction does not mediate the relationship between emotional intelligence, job performance and perception of organizational politics. This research provides useful managerial implications for improving human resources, which good companies can apply in developing training programs to improve employee skills, especially for young employees (20-25 years).